1991
DOI: 10.1002/cne.903070409
|View full text |Cite
|
Sign up to set email alerts
|

Development of the calcium‐binding proteins parvalbumin and calbindin in monkey striate cortex

Abstract: The development of immunoreactivity for the calcium-binding proteins parvalbumin (PV) and calbindin-D28K (Cal) was studied in Macaca nemestrina striate cortex from fetal (F) 60 days to postnatal (P) 5 + years. We correlated changes in PV and Cal staining patterns with the well-documented developmental sequence for primate striate cortex neuron generation and maturation, synaptogenesis, and thalamocortical axon interactions in an attempt to deduce a functional role for these proteins. Our major findings is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
1
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 83 publications
18
115
1
1
Order By: Relevance
“…The loss of CB-ir in a distinct population of neurons was pronounced in the superficial layers 2 and 4B of the denervated ODCs, where some of the weakly stained cells disappeared. Lightly labeled neurons have been shown to be pyramidal cells (Celio, 1990;Hendrickson et al, 1991;DeFelipe & Jones, 1992), and the presence of mRNA for CB was confirmed with in-situ hybridization (Sequier et al, 1990). We could not differentiate between the down regulation of the intracellular protein concentration by functional inactivation of these cells and their disappearance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The loss of CB-ir in a distinct population of neurons was pronounced in the superficial layers 2 and 4B of the denervated ODCs, where some of the weakly stained cells disappeared. Lightly labeled neurons have been shown to be pyramidal cells (Celio, 1990;Hendrickson et al, 1991;DeFelipe & Jones, 1992), and the presence of mRNA for CB was confirmed with in-situ hybridization (Sequier et al, 1990). We could not differentiate between the down regulation of the intracellular protein concentration by functional inactivation of these cells and their disappearance.…”
Section: Discussionmentioning
confidence: 91%
“…VanBrederode et al (1990) have demonstrated that very few GABAergic neurons contain both PV and CB, indicating that these mark specific subsets of interneurons. Whereas the occurrence of PV is restricted to GABAergic neurons, CB antibodies also lightly label some non-GABAergic pyramidal neurons (DeFelipe & Jones, 1992;Ferrer et al, 1992;Hendrickson et al, 1991;Sequier et al, 1990;VanBrederode et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Also, work by Conde and colleagues (Conde et al 1996;Cornelissen & Greenlee, 2000), using analysis of the laminar distribution of the calcium-binding proteins, calbindin-D28k and parvalbumin, demonstrated a hierarchical maturation of the ventral stream in the macaque, and has been used to correlate with specific events in cortical development, such as the formation of synapses and the onset of activity (Hendrickson et al 1991). For example, the expression of calbindin-D28k was associated with the establishment of synaptic connectivity, whereas the expression of parvalbumin was associated with the onset of visually driven activity (Hendrickson et al 1991).…”
Section: Cellular and Functional Maturationmentioning
confidence: 99%
“…control of pyramidal cell excitability (Blümcke et al, 1990;Cauli et al, 1997;DeFelipe et al, 1989DeFelipe et al, , 1993Hendrickson et al, 1991;Hendry et al, 1989;Lewis and Lund, 1990). Thus, it is expected that any alteration in the functional properties of the PVir interneurones will modify local inhibition, which eventually may affect the collective activity of the whole neuronal network.…”
Section: The Proportions Of Electrophysiologically Characterized Typementioning
confidence: 99%